Problems of legislative fixing the introduction of probation in Ukraine - Автухов, К. А. (Theory and practice of jurisprudence, 2016)
Analyzed the prospects of the law on probation Institute in Ukraine. The main problematic aspects introduction of probation. Proposed possible way to address disputes integration into the legal system Patriotic Institute of probation. The question of as sources of penal law considered.